The Creation of a Natural History Display at the Yıldız Palace by Fausto Zonaro and Hüseyin Zekâi Paşa - Müjde Dila Gümüş (Sanat Tarihi Yıllığı)
Related to the increasing interest in natural history in Europe in the 19th century, natural history collections were established in various institutions in the Ottoman Empire. Yıldız Palace was among the collection centers during Abdülhamid II’s reign (r. 1876-1909). The Sultan's collection used to be exhibited in the natural history museum within Yıldız Palace and at various points of the palace. The collection items were distributed to multiple educational institutions, mainly to the Ministry of Education, following Abdülhamid II's dethronement. This article focuses on two glass cabinets designed as natural history displays with landscape paintings on the interior surfaces and taxidermized birds inside. The cabinets were assembled at Yıldız Palace at the beginning of the 20th century, and have been preserved in the Istanbul University Faculty of Science since the 1930’s. Besides being examples of the display practices at Yıldız Palace, the cabinets are relevant in an art historical aspect since the paintings in them carry Fausto Zonaro’s, Hüseyin Zekai’s, Halid’s (Naci), and A. Nicot’s signatures. The cabinets exemplify a unique collaboration of four artists, each of whom had served in Yıldız Palace with different titles during Abdülhamid II’ reign. Within this article’s scope, the cabinets mentioned, which have yet to be examined in an art historical context and have been overlooked in the literature on related painters, are introduced in detait, emphasizing the paintings they carry. In relation to the critical importance of Yıldız Palace as a self-representation medium for Abdülhamid II, it is argued that natural history displays at the palace were a component of the modern appearance of the Sultan. The primary sources of the study consist of publications and archival documents from the Abdülhamid II era, photographs from Yıldız Albums, and inventory records of Istanbul University